(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
The main objective of this article is to provide insights on how applications can interact with each other on the Web using Web services. The article is devoted to Web services and their basics, as well as to technologies such as REST-compliant (RESTful) and arbitrary (XML, SOAP, WSDL, UDDI, XML-RPC) that are used to implement them.